A multimodalidade em atividades de leitura no livro didático de língua portuguesa do ensino fundamental anos finais: contribuições para o letramento visual? - Albuquerque, Emanuel Artur de (2015)
This research descriptive and analytical nature, quantitative and qualitative, discusses a few points related to the processing of multimodal genres in reading activities, particularly reading promotion for encouragement of visual literacy in Textbook of Portuguese Language (LDP). Therefore, we analyzed the work with multimodal genres (visual and verbal-visual), present in the reading activities of a collection of textbook Elementary School Portuguese final year, selected from its increased use in public schools municipal education network of the city of Bom Jardim - Pernambuco serving the second segment of elementary school. We select our categories of analysis based on semantic relationships of "redundancy", "dominance" and "complementarity" of Santaella and relationships of "inferiority", "superiority" and "equality" of Fonte and Caiado to verify the relationship of meaning between image and text in multimodal genres; note also the support the parameters of activities designed by Costa to understanding the capacities mobilized in reading activities of multimodal genres. We had to analyze the treatment of multimodal genres (visual and verbal-visual) present in the reading activities of a parsed collection favors the visual literacy. To do this, we consider the discursive enunciation assumptions of dialogical approach of Bakhtin; and the theoretical assumptions of multimodality supported by Kress and Van Leeuwen, Dionísio and Santaella. Data analysis revealed that the incidence of multimodal genres, whose verbal utterances exploit the multimodal aspects of the images in the reading activities in four copies of the didactic collection is very small, considering that the variety of genres multimodal (visual and verbal-visual ) these activities is negligible. However, we believe that investigated didactic collection favors the visual literacy, because, even with a higher incidence of genres whose verbal materiality proved semantically higher, with statements that did not promote the imagery reading, there were other activities (with multimodal genres fewer incidents) that contemplated semantic reflections on the visual semiotic code, mobilizing readers capabilities to the peculiarities of multimodal genres (visual and verbal-visual). We realize that the LDP 6th grade reading activity with the more common genre, painting, took place satisfactorily. However, in the LDP's reading activities of the 7th grade (with gender verb-visual tale), 8th grade (chronic gender verb-visual) and 9th grade (chronic visual verb gender) that work was not satisfactory. It is noteworthy that the four copies have, albeit in small quantities, activities with genres that have image in its composition and its statements exploit their discursive aspects. We hope that this study may contribute to considerations about the need for a reader training that shows the importance of visual literacy and teaching and learning conducive to the development of specific skills for reading multimodal genres.